2012
DOI: 10.4172/2157-7633.s1-005
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Engineered Mesenchymal Stem Cells Influence Gene Expression in Donor Cardiomyocytes and the Recipient Heart

Abstract: Aims: Human embryonic stem cell-derived cardiomyocytes (hESC-CMs) or mesenchymal stem cells (MSCs) facilitate post-infarct recovery, but the potential benefit of combination therapy using MSCs and hESC-CMs has not been examined. Our objective was to define the gene expression changes in donor and host-derived cells that are induced in vivo after co-transplantation of cardiomyocytes with and without mesenchymal stem cells expressing the prosurvival gene heme oxygenase 1. Methods and results: Human MSCs were eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 50 publications
0
1
1
Order By: Relevance
“…However, the therapeutic effects of cell combinations in individual studies were rather heterogeneous. Kearns-Jonker et al showed that co-transplantation of human MSC and ESC-derived CM was more beneficial than transplantation of CM alone in inducing the expression of genes in host cells that encode for factors that promote cardiac repairs, such as hepatocyte growth factor or IGF-1 (45). Notably, in contrast to our findings, synergistic effects from co-transplantation with respect to cardiac function (LVEF) have not been observed.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…However, the therapeutic effects of cell combinations in individual studies were rather heterogeneous. Kearns-Jonker et al showed that co-transplantation of human MSC and ESC-derived CM was more beneficial than transplantation of CM alone in inducing the expression of genes in host cells that encode for factors that promote cardiac repairs, such as hepatocyte growth factor or IGF-1 (45). Notably, in contrast to our findings, synergistic effects from co-transplantation with respect to cardiac function (LVEF) have not been observed.…”
Section: Discussioncontrasting
confidence: 97%
“…Our study quantitatively assesses the effect of co-transplanted MSC on survival and therapeutic effect of iPS-CM by serially and non-invasively monitoring the retention kinetics of viable luciferase-expressing CM using BLI and cardiac function via MRI. Among previous studies comparing the effects of single and combined cell therapies in animal models of MI (41,(43)(44)(45)(46)(47)(48)(49), only Kearns-Jonker et al investigated the added benefits of MSCs and ESC-derived CMs in a rat model of MI but they did not quantify cell retention (45). Ye and coworkers used quantitative PCR (qPCR) to assess cell retention in their study comparing therapeutic effects of human iPS-CM alone or in combination with iPSC-derived endothelial cells and smooth muscle cells in a pig model of ischemia/reperfusion injury (41).…”
Section: Discussionmentioning
confidence: 99%